Comparison Between Confined and Unconfined Laser Peening Effect on the Fatigue Life of Composite Materials - Al- Khazraji, Ahmed N.; Mutasher , Ammar A. (Iraqi Journal of Science, 2020)
Mechanical Engineering Department/ University of Technology- Baghdad. Confinement layer is considered as the most important parameter during the laser shock peening (LSP) treatment. In this paper, its effect on the surface treatment effectivity of composite materials was investigated. The composite used in this research was fabricated using hand lay-up as a manufacturing process. The matrix material was built from unsaturated polyester resin and reinforced with 2.5% volume fraction of micro particles of aluminum powder. Fatigue test was conducted at room temperature with constant amplitude stress and a stress ratio of R =-1, before and after LSP treatment. LSP was applied with and without confinement layer at the same level of energy after the specimens were coated with a black paint. The results manifested that the laser peening without confinement layer increased the endurance limit by about 13.296% compared with the untreated state. Whereas using water as a confinement layer during treatment reduced the endurance strength by about 18.133% compared to the untreated state. Also, it was observed that the difference between confined and unconfined LSP effects on the endurance limit was about 31.429%.